A Cross Sectional Study to Estimate Occupational Stress among Higher Secondary School Teachers in Thalassery, Kerala - Krishna Raj; Sushrit A Neelopant; Manisha Wadhwa; Pratibha Dabas (Medsci Publications, 2022)
Background: Changing norms have overburdened the educators. Our study aims to assess the levels of occupational stress among higher secondary school teachers and demographic, academic characteristics and relevant factors influencing it. Methodology: Cross sectional study was conducted in Thalassery block of Kannur district, Kerala. The block comprised of 38 schools with 516 teachers. Overall, 484 teachers participated in the study. Modified 'Manual for teacher's occupational stress scale' questionnaire was used. Results were analyzed using Chi square test, 't' test and one way ANOVA. Results: Males were 155 (32%) and females were 329 (68%). The mean age was 40.6 years. Four-fifth (81%) were from government and one-fifth (19%) were from private schools. Majority, 268 (55%), of teachers were found to have mild occupational stress. While, 171 (35%) had moderate stress and 45 (9%) had severe occupational stress. Stress was linked to vast syllabus, time constraint, outside interference, students' behavior, poor infrastructure and favoritism from authorities. Increased teaching experience and rising position in school were significantly associated with stress. Conclusion: All higher secondary school teachers in Thalaserry block of Kannur, Kerala felt occupational stress. Majority (55%) had mild stress, 35% had endured moderate and 9% suffered severe stress.